How regulation and competition influence discrimination in broadband traffic management: a comparative study of net neutrality in the United States and the United Kingdom - Cooper, A (2014)
Telecommunications policy debates concerning the contentious issue of net neutrality have revolved around a number of broadband network operator behaviors, including discriminatory traffic management – differential treatment of network traffic associated with different Internet applications for the purpose of managing performance. Some stakeholders have advocated for regulatory intervention to prevent network operators from discriminating to the detriment of independent application innovation. Others would prefer to rely on competition between network operators to discipline operator behavior. Fixed-line broadband markets in the United Kingdom and the United States have differed substantially with respect to discrimination, competition, and regulation. The UK has experienced intense competition and pervasive discriminatory traffic management without triggering regulatory activity. The US has seen much less discrimination, limited competition, and regulatory threat followed by regulatory intervention. This thesis uses elite interviews, participant observation, and documentary analysis in a comparative study of these two cases between the mid-2000s and 2011 to determine why network operators take up discriminatory traffic management (or not) and how competition and the regulatory environment affect traffic management outcomes. This thesis demonstrates that network operators take up discriminatory traffic management primarily to control cost, performance, or both. Competition promotes rather than deters discrimination because it drives broadband prices down, encouraging operators to manage high-volume applications whose traffic incurs high costs. Regulatory threat can be sufficient to counteract these desires, but in its absence and without concerns vocalized by interest groups, discriminatory approaches endure. Telecommunications regulators intervene to safeguard nondiscrimination when they conceive of their remits as encompassing social and industrial policymaking, are ambivalent about litigation risk, and are driven by their leaders’ reputational agendas, as in the case of the Federal Communications Commission. With a narrower perception of its remit and more concern for its organizational reputation, Ofcom exemplifies the characteristics that inhibit traffic management regulation.